Development of Synthetic Peptides as Functional Probes for the Lipoprotein Biosynthesis Pathway in Bacteria - Bowen, Katherine (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2021)
Protein lipidation is a critical post-translational modification that occurs in all bacteria. The essential enzymes involved in this modification are exclusive to bacteria and have demonstrated potential as antibiotic targets. This thesis, entitled Development of Synthetic Peptides as Functional Probes for the Lipoprotein Biosynthesis Pathway in Bacteria , explores the synthesis of functionalised lipopeptide-based probes to investigate the enzymes involved in this pathway. The work described in this thesis is divided into 7 chapters. Chapter 1 provides a brief historical overview of the antibiotic era and highlights the importance of continual antibiotic development. The structural variations between lipoproteins that are native to Gram-negative and Gram-positive bacteria are presented and the enzymes responsible for these modifications are introduced. Previous investigations into these enzymes as antibiotics targets are reviewed with a focus on the barriers to further development. Following this, existing synthetic and recombinant routes to access bacterial lipoproteins and lipopeptides are summarised. The chapter concludes by detailing advances in the field of peptide science that have provided novel opportunities in the synthesis of functionalised lipoprotein derivatives. In Chapter 2 we develop a novel Förster resonance energy transfer (FRET)-based lipopeptide probe which is ultimately utilised in a high-throughput assay for lipoprotein signal peptidase II (LspA). This chapter begins by investigating the synthesis of lipopeptides via the linear incorporation of a diacylglycerol-modified cysteine residue into a peptide sequence through solid-phase peptide synthesis. This initially involves the production of a lipidated cysteine residue. To this aim, two synthetic routes to this modified amino acid are presented. The introduction of this residue into a peptide sequence is explored, in addition to dual functionalisation of the peptide with multiple fluorophores. Various peptide sequences are prepared and screened for activity with LspA to facilitate the development of a high-throughput FRET-based assay for this endopeptidase. In the second part of this work, detailed in Chapters 3 and 4, we utilise the synthetic strategy presented in Chapter 2 to access peptides containing an N-terminal diacylglycerol-modified cysteine residue. Such peptides mimic the product of the LspA peptidase reaction and thus are primed to probe the activity of the subsequent enzymes in the biosynthetic pathway, namely apolipoprotein N-acyltransferase (Lnt) and lipoprotein intramolecular transacylase (Lit). In Chapter 3 we investigate the synthesis of lipidated cysteine derivatives to explore the minimal structural requirements for Lnt recognition. These insights facilitate the design of a fluorescent peptide substrate which is used to develop a novel functional assay for this enzyme. In Chapter 4, we utilise synthetic derivatives of this Lnt substrate to probe the mechanism of acyl transfer mediated by Lit. A novel assay is developed for this recently discovered acyltransferase, and we unambiguously characterise the product of the Lit reaction. To achieve this, a deuterium labelled fluorescent substrate of Lit is produced via regioselective acylation of the glyceryl functionality and selective transfer of the deuterium labelled sn-2 acyl chain by Lit is demonstrated using nuclear magnetic resonance (NMR) analysis. This chapter concludes by utilising paramagnetic NMR to show the capacity of Cu(II) to selectively interact at the N-terminus of apolipopeptides. In Chapter 5 we detail a novel synthetic route to diacylglycerol-modified peptides. The convergent methodology we report involves the late-stage modification of peptides via liposome-mediated thiol-Michael addition of a lipidated thiol to a dehydroalanine containing peptide. This affords a native diacylglycerol modification at the resultant cysteine residue. Additionally, we explore further applications of dehydroalanine, utilising this amino acid in a novel peptide ligation methodology to extend the concept of native chemical ligation. A novel on-resin route to thioester formation through β,γ-C,S thiol-Michael addition of thioacids to dehydroalanine containing peptides is investigated. This reaction yields a cysteinyl thioester which undergoes S-to-N acyl transfer through a 5-membered cyclic intermediate to afford a native peptide bond at the ligation site. In Chapter 6 we report the overall conclusions of this work and outline the future direction of this research. Finally, in Chapter 7 the experimental procedures used in this work are provided along with the associated characterisation for the compounds synthesised.
APPROVED
Keywords: Lipopeptide synthesis; Bacterial lipoproteins; Antibiotic resistance; FRET